2003
DOI: 10.1017/s0031182003004116
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol influences the hostparasite interaction between the rainbow trout (Oncorhynchus mykiss) and the crustacean ectoparasite Argulus japonicus

Abstract: The host-parasite interaction between the rainbow trout Oncorhynchus mykiss and the fish louse Argulus japonicus was investigated by administering low levels of dietary cortisol before infecting the fish with low numbers of the parasite. After 24 h, the dietary cortisol treatment elevated blood cortisol and glucose levels and stimulated the synthesis of secretory granules in the upper layer of skin cells. Infection with 6 lice per fish caused skin infiltration by lymphocytes, also in areas without parasites. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
2
10
1
Order By: Relevance
“…Positive correlations have previously been found between cortisol and lysozyme in Atlantic salmon and rainbow trout [21]. Small increases in cortisol, as seen in uninfected fish, can have an immunostimulatory effect [30]. As TGFb is a potent inhibitor of cytotoxic T lymphocyte activation, which involves MH class I molecule presentation, a negative correlation between the levels of these two genes is not unexpected [39].…”
Section: Discussionmentioning
confidence: 94%
“…Positive correlations have previously been found between cortisol and lysozyme in Atlantic salmon and rainbow trout [21]. Small increases in cortisol, as seen in uninfected fish, can have an immunostimulatory effect [30]. As TGFb is a potent inhibitor of cytotoxic T lymphocyte activation, which involves MH class I molecule presentation, a negative correlation between the levels of these two genes is not unexpected [39].…”
Section: Discussionmentioning
confidence: 94%
“…Outside of resource provisioning, blood glucose levels and subsequent glucocorticoids can also be a sign of stress. Studies have found evidence connecting parasite load to glucocorticoid and stress levels (Haond, Nolan, Ruane, Rotllant, & Wendelaar Bonga, 2003;Raouf, Smith, Brown, Wingfield, & Brown, 2006). Glucocorticoids can also regulate immune function as certain concentrations can either enhance or inhibit certain immune functions, such as immunity or inflammation (Cain & Cidlowski, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosterone inhibition in hellbenders could be beneficial for the leeches. For instance, fish with lower plasma cortisol concentrations had higher copepod infections, likely due to suppression of cortisol-stimulated changes in the skin that can help to prevent parasite infection (Haond et al, 2003). Additionally, there is some evidence that parasites can manipulate host hormones to increase their success by reducing host immune responses, or by directly utilizing host hormones for growth and reproduction (Escobedo et al, 2005).…”
Section: Leeches and Trypanosomesmentioning
confidence: 99%